2007
DOI: 10.1007/s00231-007-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

A study of nucleate boiling and critical heat flux with EHD enhancement

Abstract: Abstract. The paper describes results from an experimental and theoretical study of the effect of an electric field on nucleate boiling and the critical heat flux (CHF) in pool boiling of R123 at atmospheric pressure on a horizontal wall with a smooth surface.Two designs of electrode (parallel rods and wire mesh) were used.The experimental data exhibit some differences from the data obtained by other researchers in similar experiments on a wall with a different surface finish and with a slightly different desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 39 publications
2
31
0
2
Order By: Relevance
“…They indicated that a slight deposit on the boiling surface can substantially shift the boiling curve and increase CHF. Also, Hristov et al [5] reconfirmed that no hysteresis was shown with Fig. 7.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…They indicated that a slight deposit on the boiling surface can substantially shift the boiling curve and increase CHF. Also, Hristov et al [5] reconfirmed that no hysteresis was shown with Fig. 7.…”
Section: Methodsmentioning
confidence: 54%
“…Also, the EHD has been recognized as an efficient active method to increase the heat exchange. The CHF for saturated boiling of R123 on polished copper wall at atmospheric pressure was increased up to 64.6 W/ cm by the application of a high dc voltage of 25 kV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Heat flux decreased with the increasing electric field intensity at the same degree of superheat. Although this deterioration in heat flux was also recorded by Hristov et al [18], but they did not analyze this phenomenon because this region existed in a small portion in the boiling curve. Typical nucleation region corresponding to the middle superheat temperature of 20°C < DT < 30°C showed no interaction between bubbles.…”
Section: Boiling Curves For Smooth Heating Surfaces Under An Electricmentioning
confidence: 94%
“…, 5) as: If the velocity y 1 is supported on Γ 12 (which implies the interfaces between the fluids and the solid substrate remain unchanged if δ is small enough), without loss of generality we can assume the velocity y 1 is normal to the interface Γ 12 and given by y 1 = vn. Then it is clear that T3 = T4 = 0, 10) and (e.g. [47])…”
Section: An Equivalent Variational Formulationmentioning
confidence: 99%